Nepenthes di Gunung Sibuatan, Provinsi Sumatera Utara, Indonesia - Mhd. Rafi'i Ma'arif Tarigan; Yusran Efendi Ritonga (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2021)
ABSTRACT                                                                                          This research aims at determining the types of Nepenthes in the Mount Sibuatan area, Karo District, North Sumatera Province, Indonesia. The research was conducted in March 2021, using explorative research methods. Samples collected in fresh form. Identification was carried out using the procedures of book references Flora of Java Volume I, Nepenthes of Sumatra, Field Guide to the Pitcher Plants of Sumatra and Java. The results of the research found five species of Nepenthes namely N. pectinata Danser, N. spectabilis Danser, N. tobaica Danser and two species are natural crosses, namely N. pectinata x spectabilis, and N. pectinata x tobaica at an altitude of 1,796-2,457 m asl with a temperature 15.3°C-21.2°C. Key words: Nepenthes, Characterization of Nepenthes, Mount Sibuatan